Neuroborreliosis mimicking demyelinating disease of the central nervous system: case reports - N. Giedraitienė; A. Lisinskaitė; A. Klimašauskienė (Neurologijos seminarai)
We present two patients with neuroborreliosis initially considered as demyelinating disease of the central nervous system. The first patient developed facial numbness on the right side, diplopia and dizziness that lasted about half a year. Magnetic resonance imaging of the brain showed confluent hyperintense lesions and visual evoked potentials revealed prolonged latencies of the P wave. The second patient developed weakness, numbness and pain in the left hand that lasted several weeks. Magnetic resonance imaging of the cervical spine demonstrated hyperintense lesions commonly found in multiple sclerosis. In both cases, positive serology for Borrelia burgdorferi was an indicator of past infection. However, the cerebrospinal fluid analysis showed proteinorrhachia and lymphocytic pleocytosis and the presence of specific IgM and IgG antibodies in the cerebrospinal fluid confirmed the diagnosis of neuroborreliosis. The clinical symptoms, abnormal cytological, biochemical and immunological cerebrospinal fluid findings in combination with good response to antibiotic therapy confirmed the diagnosis of neuroborreliosis in our patients.